Governance mechanisms and metrics for digital platform workers : Multiple case study of digital labour platforms - Ahopelto, Hanna (My University, 2023)
Aim: This study aims to reveal which governance mechanisms and their metrics digital labour platforms use and how they are used to govern platform workers. Moreover, this study's purpose is to analyse three different digital labour platform companies related to the governance of platform workers. The study aims to form and test a framework for the digital labour platform governance mechanisms and their metrics based on a literature review and empirical findings. Framework: The study framework combines traditional firm governance, digital platform governance and crowdwork governance theories. In addition, the concepts of control and coordi-nation in governance mechanisms are presented in the literature review of governance theory. The themes are combined to form a framework for digital labour platform governance mechanisms for platform workers. Methodology: The empirical research section is formed with qualitative research and multiple case study method. The approach of the study is subjectivist. Moreover, interpretivism and critical realism views are used because they fit the people-oriented and multi-dimensional research theme. The research data is collected with interviews of the case companies’ representatives who were in positions to know the subjects. The findings reveal what and how governance mechanisms and metrics are used in digital labour platforms to govern platform workers. In addition, the results show two new governance mechanisms: platform worker training and activity monitoring. Governance mechanisms identified include access control, activity monitoring, task management, incentive management, contract management, and training in every case company. In contrast, only two companies used reputation monitoring, quality control, and behavioural control. The findings differ somewhat between the case companies. The reason for the variation between the companies might be due to the variety in the level of autonomy and skill levels of platform workers. The governance mechanisms and metrics findings are brought together into a framework. Also, this study revealed new information about governance metrics of digital labour platforms, which had a little information in the literature. Thus, the governance metrics found in this study give significant new knowledge about the subject. They help to show how firms can use the data for platform worker governance in digital platforms. For instance, user logins, system usage, and profile completion rate measure platform workers' activity. These findings can help digital labour platform companies better understand many possibilities in ways to govern digital labour workers.

Tavoite: Tämän tutkimuksen tavoitteena on selvittää digitaalisten työtä välittävien alustojen alustatyöntekijöihin kohdistuvia hallintamekanismeja ja niiden mittareita. Tarkoituksena on analysoida kolmen case yrityksen alustatoimintaa suhteessa alustatyöntekijöiden hallintaan. Tutkimuksessa muodostetaan viitekehys digitaalisten alustojen hallintamekanismeista ja niiden mittareista kirjallisuuskatsauksen ja empiirisen tutkimuksen perusteella. Viitekehys: Tämän tutkimuksen viitekehyksessä yhdistyy perinteisten yritysten hallintamekanismeja, joukkotyöhön liitettyjä hallintamekanismeja sekä digitaalisten alustojen jo tiedettyjä hallintamekanismeja. Lisäksi kontrollin ja koordinaation konseptit liittyen työntekijöiden hallintaan esitetään kirjallisuuskatsauksessa ja ne liitetään osaksi viitekehystä. Myös joitain vähän tiedettyjä hallintamittareita on lisätty viitekehykseen. Näistä teemoista muodostuu tutkimuksen viitekehys alustojen alustatyöntekijöille suunnatuille hallintamekanismeille ja niiden mittareille. Metodologia: Empiirinen tutkimus koostuu laadullisesta tutkimuksesta ja usean tapaustutkimuksen menetelmästä. Tutkimuksen lähestymistapa on subjektiivinen. Lisäksi interpretivismin ja kriittisen realismin lähestymistapoja käytetään tutkimuksen analysoimisessa, sillä ne soveltuvat tutkimuksen ihmislähtöiseen ja moniulotteiseen teemaan. Tutkimuksen aineistonkeruumenetelmänä käytetään case yritysten edustajien haastatteluja. Tulokset: Tutkimuksen tulokset osoittavat, että mitä ja kuinka hallintamekanismeja ja niiden mittareita käytetään digitaalisilla alustoilla alustatyöntekijöiden hallitsemiseen. Tulokset osoittavat myös kaksi uutta hallintamekanismia: alustatyöntekijöiden kouluttamisen ja aktiivisuuden valvomisen. Hallintamekanismeista tunnistettiin pääsyn valvonta, tehtävänhallinta, sopimushallinta, ja kouluttaminen kaikissa case-yrityksissä. Sen sijaan vain kahdessa yrityksessä tunnistettiin maineen valvonta, laadun valvonta ja käyttäytymisenhallinta. Syyt vaihteluihin yritysten välillä saattavat johtua alustatyöntekijöiden erilaisista autonomian tasoista ja taitotasoista. Tulokset hallintamekanismeista ja niiden mittareista digitaalisilla alustoilla on kerätty yhteen viitekehykseen. Tutkimuksessa selvisi uutta tietoa hallintamittareista, joista ei ollut aiemmin paljon tietoa kirjallisuudessa. Siksi hallintamittarit, jotka onnistuttiin löytämään tässä tutkimuksessa antavat merkittävää uutta tietoa aiheesta. Ne auttavat yrityksiä ymmärtämään kuinka hyödyntää dataa alustatyöntekijöiden hallitsemisessa. esimerkiksi aktiivisuuden valvomisessa voidaan käyttää mittareina käyttäjän sisäänkirjautumisia, järjestelmän käyttämistä, ja profiilin valmiusastetta. Tulokset auttavat yrityksiä huomaamaan monipuolisesti mahdollisuuksia alustatyöntekijöiden hallitsemisessa ja ottamaan huomioon alustatyöntekijöiden autonomian ja osaamistasot hallintamekanismeja valittaessa.
Keywords: platform economy; alustatalous; alustat; hallinnointi; mekanismit; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development